Trust as mediator of the relationship between retention factors and organisational commitment in the Malaysian ICT sector - Ahsan, Mst. Nilufar (2014)
One of the biggest challenges for the most knowledge-based organisations in these highly competitive era is retaining knowledge workers. Now-a-days company can no longer rely on the loyalty of knowledge workers, who are highly skilled and easily marketable. Understanding knowledge workers and what makes them remain and continue to contribute to the organization is an important task for most managers. Thus, this exploratory study examine the most and least important retention strategies used by MSC status companies in Malaysia, for encouraging knowledge workers to be committed and continue their services. The research was motivated by the situation of software companies, those always facing lack of commitment of their skilled workers. The research adopted a quantitative method approach. In the first phase, the literature review identified the retention factors as relevant to the study of human resource management (HRM). Then this research also identified a mediator variable. All together seven retention factors i.e. compensation, training and development, career opportunity, supervisor support, job autonomy, work/life policies and skill varieties and trust were identified as mediating construct in this research.